DNA barcoding deep-water zooplankton from the Gulf of Alaska, North Pacific Ocean - Questel, Jennifer M.; Smoot, Caitlin A.; Collins, Allen G.; Lindsay, Dhugal J.; Hopcroft, Russell R. (Frontiers in Marine Science, 2025)
DNA barcoding is a method of identifying individual organisms using short DNA fragments matched to a database of reference sequences. For metazoan plankton, a high proportion of species that reside in the deep ocean still lack reliable reference sequences for genetic markers for barcoding and systematics. We report on substantial taxonomic and barcoding efforts across major zooplankton taxonomic groups collected from surface waters to the rarely sampled abyssopelagic zone (0 – 4300 m) from the Gulf of Alaska, North Pacific Ocean. Over 1000 specimens were identified, from which the mitochondrial 16S and COI and nuclear 18S rRNA genes were sequenced. In total, 1462 sequences for 254 unique taxa were generated, adding new barcodes for 107 species, including 12 undescribed species of cnidarians, that previously lacked DNA sequences for at least one of the three genes. Additionally, we introduce the use of a new Open Nomenclature qualifier deoxyribonucleic acid abbreviation DNA (e.g., Genus DNA species, DNA Genus). This qualifier was used for specimens that could not be morphologically identified but could be assigned a low-level taxonomic identification based on the clustering of DNA barcode genes using phylogenetic trees (100% bootstrap support), where at least one of the sequences in that clade could be referred to a physical specimen (or photographs) where identification could be corroborated through morphological analyses. DNA barcodes from this work are incorporated into the MetaZooGene Atlas and Database, an open-access data and metadata portal for barcoding genes used for classifying and identifying marine organisms. As environmental sequencing (i.e., metabarcoding, metagenetics, and eDNA) becomes an increasingly common approach in marine ecosystem studies, continued population of such reference DNA sequence databases must remain a high priority.